Till murder do us part [compact disc, unabridged] : true-crime thrillers - Patterson, James, 1947- (Hachette Audio, 2021)
Till murder do us part: Kathi Spiars can't believe she's found such a good man to marry as Stephen Marcum. Twelve years later, she starts to suspect that he isn't who he says he is. As she digs into his past, she doesn't realize that learning the truth will lead to a lifetime of fear and hiding.